Establishment of Clonal MIN-O Transplant Lines for Molecular Imaging via Lentiviral Transduction & In Vitro Culture - Boucher, David L.; Chen, Jane Qian; Cherry, Simon R.; Borowsky, Alexander D. (PLOS ONE, 2012)
As the field of molecular imaging evolves and increasingly is asked to fill the discovery and validation space between basic science and clinical applications, careful consideration should be given to the models in which studies are conducted. The MIN-O mouse model series is an established in vivo model of human mammary precancer ductal carcinoma in situ with progression to invasive carcinoma. This series of transplant lines is propagated in vivo and experiments utilizing this model can be completed in non-engineered immune intact FVB/n wild type mice thereby modeling the tumor microenvironment with biological relevance superior to traditional tumor cell xenografts. Unfortunately, the same qualities that make this and many other transplant lines more biologically relevant than standard cell lines for molecular imaging studies present a significant obstacle as somatic genetic re-engineering modifications common to many imaging applications can be technically challenging. Here, we describe a protocol for the efficient lentiviral transduction of cell slurries derived from precancerous MIN-O lesions, in vitro culture of “MIN-O-spheres” derived from single cell clones, and the subsequent transplantation of these spheres to produce transduced sublines suitable for optical imaging applications. These lines retain the physiologic and pathologic properties, including multilineage differentiation, and complex microanatomic interaction with the host stroma characteristic of the MIN-O model. We also present the in vivo imaging and immunohistochemical analysis of serial transplantation of one such subline and detail the progressive multifocal loss of the transgene in successive generations.